A surface roughness prediction model for laser beam cutting (LBC) on acrylic sheets - Mohd Arif, Mokti (2008)
The present thesis discusses the development of the statistic model surface roughness for acrylic sheet on laser beam cutting and the effect of laser beam cutting (LBC) parameters towards acrylic sheet surface roughness. The model are developed by using the response surface methodology (RSM) to study the effect of cutting parameters (power, laser speed, gap distance and material thickness) on acrylic sheets surface roughness. The model of the experiment is performed with using Box- Behnken design which it will arrange all the cutting parameters with suitable combination that needed for experiments performance. The affect of input factors and the interaction between these factors are also investigated in this study. It was found that the interaction of these parameters (power, laser speed, gap distance and material thickness) with surface roughness was extremely strong. The predictive models in this study are believed to produce value of the surface roughness. The predicted model for first order and second order for this model is performed with using MINITAB software. MINITAB will able to give solution for many data analysis and then predicted model will come out after finish all the analysis steps.